A study of learners' situational vulnerability: new teachers in Scotland - Rachel Shanks (University of Aberdeen, School of Education, 2014)
"In this paper an example of vulnerable learners in the workplace is explored, namely new teachers in Scotland. New teachers may not have been regarded as vulnerable learners before but it will be argued that because they are subject to situational vulnerability at the beginning of their careers they are vulnerable learners. In their first year teachers are new to their school as well as new to their profession and in Scotland new teachers are also vulnerable because they are on a one year fixed term contract, are working towards the Standard for Full Registration and need to obtain satisfactory references for future job applications. A sequential mixed methods study was conducted in which online questionnaires and semi-structured interviews were used to collect data from new teachers themselves. The extent to which new teachers are in a vulnerable situation was explored and how expansive practices in their learning environment could lessen their vulnerability and provide them with learning opportunities. The identification of expansive features in school learning environments demonstrates ways that new teachers' learning can be supported. With an improved understanding of the position of new teachers and ways to reduce their vulnerability in their transition from student teacher to qualified teacher, their professional learning can be enhanced."